2019
DOI: 10.1051/shsconf/20196507003
|View full text |Cite
|
Sign up to set email alerts
|

Application of fuzzy logic approach for the determination of the integral index of the implicit impact of the higher education system on regional development (on the example of Ukraine)

Abstract: In this paper the theoretical and methodological aspects of the influence of the higher education system on the socio-economic development of the regions of Ukraine are considered. On the basis of fuzzy logic approach, we have calculated the integral index of the implicit impact (IIII = I4) of the higher education system on regional development. Regions are grouped by this indicator over time. The integral indicator allowed us to identify regions with the corresponding I4 of the higher education system at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The mass nature of education is a huge factor that can be used effectively for the transfer and diffusion of entrepreneurship competencies and technological culture into society. Sotula and Denysenko (2019) showed that universities face numerous problems of transition to the European model of higher education, quality assurance system, which should be solved as soon as possible, otherwise, Ukrainian HEIs will lose completion to their neighbours.…”
Section: Theoretical Framework and Litera-ture Reviewmentioning
confidence: 99%
“…The mass nature of education is a huge factor that can be used effectively for the transfer and diffusion of entrepreneurship competencies and technological culture into society. Sotula and Denysenko (2019) showed that universities face numerous problems of transition to the European model of higher education, quality assurance system, which should be solved as soon as possible, otherwise, Ukrainian HEIs will lose completion to their neighbours.…”
Section: Theoretical Framework and Litera-ture Reviewmentioning
confidence: 99%